From Presbyopia to Cataracts: A Critical Review on Dysfunctional Lens Syndrome - Joaquín Fernández; Manuel Rodríguez-Vallejo; Javier Martínez; Ana Tauste; David P. Piñero (Journal of Ophthalmology)
Dysfunctional lens syndrome (DLS) is a term coined to describe the natural aging changes in the crystalline lens. Different alterations in the refractive properties and transparency of the lens are produced during the development of presbyopia and cataract, such as changes in internal high order aberrations or an increase in ocular forward scattering, with a potentially significant impact on clinical measures, including visual acuity and contrast sensitivity. Objective technologies have emerged to solve the limits of current methods for the grading of the lens aging, which have been linked to the DLS term. However, there is still not a gold standard or evidence-based clinical guidelines around these new technologies despite multiple research studies have correlated their results with conventional methods such as visual acuity or the lens opacification system (LOCS), with more scientific background around the ocular scattering index (OSI) and Scheimpflug densitometry. In either case, DLS is not a new evidence-based concept that leads to new knowledge about crystalline lens aging but it is a nomenclature change of two existing terms, presbyopia and cataracts. Therefore, this term should be used with caution in the scientific peer-reviewed literature.